New Uses for Traditional Buildings: The Olive Oil Mills of the Karpas Peninsula, Cyprus - Oktay Vehbi, Beser; Yuceer, Hulya; Hurol, Yonca (Taylor and Francis- Routledge, 2019)
Traditional agro-industrial buildings in rural areas reflect the way of life of past communities and their dependence on agriculture. Although conservation is critical for the transfer of knowledge about past generations and in sustaining community identity and development, many of these building types worldwide are threatened by dereliction due to the emergence of new technologies that cannot be housed in the old buildings. This study suggests that their reuse for tourism purposes, especially in countries of limited resources and opportunities, can help rural development by attracting both people and investment. The claim is exemplified by the case of traditional olive oil mills in Cyprus, which are considered significant elements of the rural landscape. The research focuses on the Karpas Peninsula, where the majority of traditional olive mills are either derelict or in poor condition, though where some have already been destroyed. A brief literature review of industrial heritage and alternative tourism forms the basis for the evaluation of the case study. The research highlights the significance of olives and olive oil for the Cypriot community, and discusses the current social and economic dynamics of the Karpas Peninsula through an examination of the potential of 18 traditional olive mills. The study suggests the reuse of traditional olive mills through alternative tourism and the development of thematic heritage routes.
This article discusses the architectural, technical and urban characteristics of the olive mills in North Cyprus and makes suggestions on their future use.
Keywords: Industrial heritage; reuse; alternative tourism; policy making; olive oil mill; Cyprus